Territorial Cooperation With Non-Eu Regions - Juan Carlos Rodriguez-Cohard; Javier Alfonso; Antonio Vázquez-Barquero (European Regional Science Association (ERSA), 2012)
Territorial Cooperation (TC) has been possible because there is a trajectory of many years of work invested by the local actors, participants who have become the architects of TC through the city or region involved. Transcontinental cooperation as studied by the European Union TERCO project is providing important lessons for understanding TC. The purpose of the presentation is to analyze the Andalusian-North of Morocco territorial cooperation during the last twenty years. Twinning cities, bilateral cooperation agreements and networks have structured participation in projects with varying degrees of impact on the economic, social, urban and environmental conditions. The initiatives have always been local and with a bottom-up approach. The management capacity of key organizations working in a descentralized way and their background on local development governance have made available the implementation of local iniciatives. The projects with the best results are those that are carried out jointly and adapt to Moroccan needs in agreement with its territorial development strategy which was previously defined. Special institutional and cultural mechanisms of developing in both sides of Mediterranean Sea were very helpful. The institutional weaknesses and the complexity of decision-making mechanism in Andalusia and Morocco can make relations difficult and therefore territorial cooperation weak. Territorial Cooperation needs to be flexible enough to respond to changes in the socio-economic environment. The case study of Andalusia-North of Morocco shows that local economic development (e.g. technological innovation or international trade) are important. These issues are usually approached through public-private coordination organizations, such as development agencies. As shown by some other case studies of the TERCO project the results of the participation of such agencies are still modest. Special attention should be given to TC with Morocco due to geo-strategic relations both with Spain and Europe. Not only are there sporadic problems of a bilateral strategic nature between Spain (EU) and Morocco at the Central Government level which can affect decentralized TC, but also, problems with illegal migration (an EU concern), and difficulties in acquiring visas to travel for the cooperating agents, could very well jeopardize TC initiatives.
Keywords: O15; O43; R58; 330; Territorial Cooperation; Local Development; Governance